Assessing Online-Shopping Influences on Customer Behaviour and Brand Loyalty in Setapak District, Kuala Lumpur, Malaysia - Tan, Yi Siang (2024)
This thesis explores the intricate relationship between customer behaviour and brand loyalty within the context of online shopping for organic food in the Setapak District, Wilayah Persekutuan, Malaysia. As the e-commerce landscape continues to evolve, understanding the dynamics of consumer interactions and their impact on brand allegiance becomes paramount for businesses operating in this digital era. The research employs a quantitative approach to gather comprehensive insights into the online shopping habits of consumers in Setapak District. Through a careful analysis of customer behavior patterns, the study aims to identify key factors influencing purchasing decisions, including product preferences, user experience, and perceived value. Furthermore, the investigation delves into the concept of brand loyalty in the online shopping environment. By examining the factors that contribute to customers' allegiance to specific brands, the research sheds light on the strategies that businesses can employ to foster and maintain customer loyalty in the competitive online marketplace. The findings of this study hold implications for businesses, policymakers, and marketers seeking to optimize their strategies in the digital retail landscape. Understanding the value of customer behaviour and brand loyalty not only enhances the effectiveness of marketing efforts but also contributes to the long-term sustainability and success of online businesses in the Setapak District and beyond.